2018
DOI: 10.2196/10327
|View full text |Cite
|
Sign up to set email alerts
|

What Do Germans Want to Know About Skin Cancer? A Nationwide Google Search Analysis From 2013 to 2017

Abstract: BackgroundExperts worldwide agree that skin cancer is a global health issue, but only a few studies have reported on world populations’ interest in skin cancer. Internet search data can reflect the interest of a population in different topics and thereby identify what the population wants to know.ObjectiveOur aim was to assess the interest of the German population in nonmelanoma skin cancer and melanoma.MethodsGoogle AdWords Keyword Planner was used to identify search terms related to nonmelanoma skin cancer a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
46
1
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 40 publications
3
46
1
11
Order By: Relevance
“…One way to investigate reasons for not using skin cancer prevention measures is to focus on the interest in skin cancer among the general population (28). As the Internet is a commonly used source of health information, search engine analysis represents a novel tool for investigating the general interest in various topics (16,(28)(29)(30)(31)(32)(33). In Germany, approximately 90% of inhabitants use the Internet (34).…”
mentioning
confidence: 99%
“…One way to investigate reasons for not using skin cancer prevention measures is to focus on the interest in skin cancer among the general population (28). As the Internet is a commonly used source of health information, search engine analysis represents a novel tool for investigating the general interest in various topics (16,(28)(29)(30)(31)(32)(33). In Germany, approximately 90% of inhabitants use the Internet (34).…”
mentioning
confidence: 99%
“…Furthermore, compared with melanoma, they cause a higher burden of disease when measured using disability‐adjusted life years . Today, KCs pose an enormous socioeconomic burden, which is likely to increase even further over the coming years considering the increasing incidence worldwide . Accordingly, effective and sustainable awareness and prevention strategies are urgently needed …”
mentioning
confidence: 99%
“…3,7 Today, KCs pose an enormous socioeconomic burden, [8][9][10][11] which is likely to increase even further over the coming years considering the increasing incidence worldwide. 12,13 Accordingly, effective and sustainable awareness and prevention strategies are urgently needed. [12][13][14] The main modifiable risk factor for KC is extensive exposure to ultraviolet radiation (UVR) of the sun, which logically leads to KC primarily occurring on light-exposed parts of the body.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, within the last few years, several publications have shown that NMSC prevention strategies like using sun protection and undergoing skin cancer screening are not highly prevalent among outdoor professionals, especially mountain guides, 10,16,17,[25][26][27][28] despite the ease of compliance and noninvasive nature of these strategies. Various reasons are conceivable for these observations, but so far most have received only limited attention in respective studies.…”
Section: Introductionmentioning
confidence: 99%